Land Acquisition for Jenelata Dam Building in Gowa; A Comparative Study - Kadir, Muh. Fiqri; HL, Rahmatiah (Mazahibuna: Jurnal Perbandingan Mazhab, 2021)
This article aims to uncover the views of Islamic law as a universal rule does not only discuss the relationship between humans and God but also the relationship between humans and other humans. The order of life in society as part of the interaction between humans creates various problems. Land becomes an object of economic driving for humans and the state whose users cannot be separated from politics and law, as well as having a function to create life together. The research method used is field research and is qualitative and comparative. Sources of data used in this study come from primary and secondary data. The result of this research is that the purpose of this land acquisition is for the public interest. In Islamic law, land acquisition for public purposes is included in one of the objectives of Islamic law (maqashid syariah). Islamic law teaches to help each other in terms of goodness, by having joint ownership of objects that have been held, the soul is calm because the needs have been provided. An object that is used as a public facility is a valuable asset so that the procurement process also uses a well-ordered system.